Can matching frictions explain the increase in Mexican unemployment after 2008? - Juan Arroyo Miranda; Roberto Gómez Cram; Carlos Lever Guzmán (Banco de México, 2014)
We use a novel data set on firm vacancies and job seekers from a Mexican government job placement service to analyze whether changes in matching frictions can explain the large and persistent increase in Mexican unemployment after the 2008 global financial crisis. We find evidence of a statistically signicant reduction in the efficiency of the matching function during the crisis. The estimated effect explains about 70 basis points of the 233 basis points observed increase in the unemployment rate. Hence, these results suggest that changes in matching frictions cannot explain most of the increase in unemployment.
Keywords: J63; J64; E24; 330; Matching function estimation; Unemployment; Vacancies